Chemically Activated Carbons from Olive Stones — Peculiarities of Pore Structure and Interpretation of Nitrogen Adsorption Data - M.A. Hourieh; M.N. Alaya; F. El-Sejariah; A.M. Youssef (Adsorption Science & Technology)
Chemically activated carbons were obtained from olive stones either by carbonization with H 3 PO 4 at 300–600°C or by carbonization with ZnCl 2 at 600°C. Nitrogen adsorption at 77 K was determined for all the activated carbons. The adsorption data were interpreted by considering some conventional adsorption models. Maximum activation with H 3 PO 4 occurred at 450°C. However, the adsorption capacities of the ZnCl 2 -activated carbons were far higher than those of carbons activated with H 3 PO 4 . Carbons activated with H 3 PO 4 or ZnCl 2 are mainly microporous with the non-micropores representing a small fraction of the total porosity. Although, the nitrogen isotherms are Langmuirian in shape, application of the Langmuir equation led to large monolayer capacities of uncertain confidence. The surface areas and micropore volumes determined by the application of the t-method of de Boer and the α S -method of Sing were comparable and were slightly higher than those determined by the application of the DR model based on micropore filling. The t-method and the α S -method are complementary to each other and would seem to give confident values because they are based on standard reference non-porous materials. The micropore region may be sub-divided into two sub-regions distinguished by the different filling mechanisms involved.